Energetic valorization of algal biomass in a hybrid anaerobic reactor. (1st March 2018) - Assemany, Paula; Marques, Isabel de Paula; Calijuri, Maria Lúcia; Lopes da Silva, Teresa; Reis, Alberto
Abstract: This study evaluated the operation of a hybrid anaerobic reactor fed with algal biomass cultivated in effluent from the brewery industry. Three stages of operation were distinguished during the 72 days of semi-continuous functioning of the reactor: Stage 1 (S1), in which algal biomass was used as substrate; Stage 2 (S2), in which 10% (v/v) of the algal biomass was substituted by olive mill wastewater (OMW); and Stage 3 (S3), in which algal biomass was heat pre-treated. During S1, a loss of solids was observed, with an increment of organic matter in the outlet. The substitution of 10% of the volume of algal biomass by OMW tripled the methane productivity obtained in the previous stage by digestion of pure algal biomass. Heat pre-treatment was not efficient in rupturing the cell wall, and consequently did not have any effect on the increase in biogas production. The complementarity of substrates in the assessed conditions led to better results than the pre-treatment of the algal biomass. Highlights: A hybrid anaerobic reactor was fed with algal biomass grown in brewery effluent. Solid loss was severely observed when digesting only algal biomass. The addition of 10% of olive mill wastewater tripled the methane productivity. Heat pre-treatment did not have any effect on the increase in biogas production. Easiness operation and cost reduction are obtained with complementary substrate.